Developmental effects in physiological stress in early adolescents with and without autism spectrum disorder. (March 2021) - Corbett, Blythe A.; Muscatello, Rachael A.; Kim, Ahra; Patel, Kunj; Vandekar, Simon
Abstract: Introduction: Humans place high value on how they are socially evaluated by others. The Trier Social Stress Test (TSST) is a well-established measure of social evaluative threat that promotes activation of the hypothalamic pituitary adrenal (HPA) axis and release of cortisol. Higher cortisol responses in typically developing (TD) adolescents are influenced by age and pubertal development especially in later stages. Children with ASD have been shown to exhibit blunted cortisol in response to the TSST although adults with ASD show a more prototypical response. The current study examined physiological stress in early adolescents with ASD and TD. It was hypothesized that TD youth would show elevated cortisol in response to the TSST influenced by age and pubertal stage. In contrast, youth with ASD would show a more diminished stress response yet still show effects for age and pubertal development Methods: The sample included 241 youth, 138 with ASD (median age = 11.25) and 103 TD (median age = 11.67). Standardized diagnostic and pubertal development (genital/breast (GB), and pubic hair (PH) stage) physical exams were performed. Salivary cortisol was collected before and after the TSST. Linear mixed effects models examined the effects of baseline cortisol, time, age, sex, pubertal stage, and diagnosis. Results: We did not find an effect of early pubertal development stage (GB or PH) on cortisol response. There was an interaction between age and TSST timepoint, showing stronger effects for older children across the timeline especially during the stressor. Finally, there was a significant diagnosis by TSST timepoint interaction characterized by a blunted cortisol stress response in youth with ASD compared to TD participants who showed higher cortisol. Discussion: We found evidence that age contributes to an increase in cortisol in response to social evaluative threat during early adolescence. TD youth exhibit an adaptive elevated stress response to psychosocial threat whereas youth with ASD do not. There may exist a developmental lag in the perception of and stress responsivity to social evaluation which may emerge in older adolescents with ASD. Highlights: Cortisol is elevated during social evaluation which increases during adolescence. Age not pubertal stage contributed to higher cortisol during early adolescence. Early adolescents with autism show blunted cortisol response compared to typical youth. There may be a developmental lag in stress response to social evaluation in autism.